Do Resident Archetypes Influence the Functioning of Programs of Assessment? - Jessica V. Rich; Warren J. Cheung; Lara Cooke; Anna Oswald; Stephen Gauthier; Andrew K. Hall (MDPI AG, 2022)
While most case studies consider how programs of assessment may influence residents' achievement, we engaged in a qualitative, multiple case study to model how resident engagement and performance can reciprocally influence the program of assessment. We conducted virtual focus groups with program leaders from four residency training programs from different disciplines (internal medicine, emergency medicine, neurology, and rheumatology) and institutions. We facilitated discussion with live screen-sharing to (1) improve upon a previously-derived model of programmatic assessment and (2) explore how different resident archetypes (sample profiles) may influence their program of assessment. Participants agreed that differences in resident engagement and performance can influence their programs of assessment in some (mal)adaptive ways. For residents who are disengaged and weakly performing (of which there are a few), significantly more time is spent to make sense of problematic evidence, arrive at a decision, and generate recommendations. Whereas for residents who are engaged and performing strongly (the vast majority), significantly less effort is thought to be spent on discussion and formalized recommendations. These findings motivate us to fulfill the potential of programmatic assessment by more intentionally and strategically challenging those who are engaged and strongly performing, and by anticipating ways that weakly performing residents may strain existing processes.